ELECTRICAL DEVICES OF SOLAR POWER PLANTS (International journal of artificial intelligence, 2025)
The rapid transition to renewable energy has placed solar power at the forefront of sustainable electricity generation. Among the critical elements of solar power plants are the electrical devices that convert, manage, distribute, and protect the generated energy. These devices form the backbone of solar power infrastructure, ensuring that solar energy is not only harvested efficiently but also delivered to end-users with safety, reliability, and quality. This abstract explores in detail the various electrical devices employed in solar photovoltaic (PV) power plants, their technical characteristics, functions, operational roles, and integration within the wider electrical grid.